Terapi Hipnosis terhadap Kecemasan dalam Kehamilan - Indah Puji Septeria; Najmah Najmah; Rizma Adlia Syakurah (Jurnal Keperawatan Silampari, 2023)
This study aims to find out how hypnosis influences anxiety in pregnancy. The research method is a literature review that seeks more information about hypnosis's effect on reducing pregnancy anxiety. The results of these studies have differences in terms of research time, research design, number of research subjects and interventions used, and intervention providers. Still, overall research consistently supports the benefits of hypnosis to calm anxiety in pregnant women and labor. In conclusion, hypnosis can reduce pain, accelerate delivery, feelings of tension, worry about bad things, fear, nervousness, anxiety, doubt, stress, and confusion, and increase feelings of satisfaction, confidence, relaxation, meaning, steady, and happiness. Keywords: Hypnosis, Anxiety, Pregnancy